Strategic Management Practices and Performance of Nepalese Commercial Banks - Agrawal, Neha; Agrawal, Niraj (Journal of Economics and Management, 2024)
The adoption of good strategic management strategies is crucial for banks to attain long-term success and maintain their competitiveness. Examining strategic management practices in Nepalese commercial banks is aim of this study. Four independent variables i.e., environmental scanning, strategy formulation, strategy execution, and strategy assessment control, as well as one dependent variable i.e., performance of Nepalese commercial banks, were primary focus of this study. This study is quantitative in nature. For the study, a causal comparative research design was chosen. To gather primary data on the factors and investigate their relationship, a survey was conducted. Simple random sampling was used to distribute self-administered questionnaires for this investigation. Data was collected from 216 respondents from among 10 commercial banks of Nepal. In the analytical section, both descriptive and inferential analyses were conducted. Data analysis was made using SPSS. With an R2 value of 0.685, the inferential analysis demonstrates that every aspect of strategic management techniques under investigation has a favourable and statistically significant effect on the operations of Nepal's commercial banks. Among the four dimensions of strategic management practices strategy formulation have the most influential role on performance of commercial banks in Nepal in financial and non-financial terms. Managers of Nepalese commercial banks should take steps to continuously apply the approaches of strategic management for long-term competitive advantage.